2016
DOI: 10.1037/edu0000115
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions as moderators of the worked example effect: When shifting is more important than working memory capacity.

Abstract: Worked examples have proven to be effective for knowledge acquisition compared with problem solving, particularly when prior knowledge is low (e.g., Kalyuga, 2007). However, in addition to prior knowledge, executive functions and fluid intelligence might be potential moderators of the effectiveness of worked examples. The present study examines the roles of the executive functions of working memory capacity and shifting, as well as the role of fluid intelligence for knowledge acquisition in the presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 65 publications
5
57
0
Order By: Relevance
“…Learners with high fluid intelligence do not need this instructional support because they can more easily use their reasoning capacity to determine which information is necessary to solve a given problem. In line with this argumentation, Schwaighofer et al (2016) found that the benefits of worked examples compared to problem solving were lower the higher fluid intelligence was. In that study, the moderating role of fluid intelligence was independent of working memory capacity and shifting.…”
Section: Aptitude Treatment Interactions In the Context Of Complex Lesupporting
confidence: 68%
See 4 more Smart Citations
“…Learners with high fluid intelligence do not need this instructional support because they can more easily use their reasoning capacity to determine which information is necessary to solve a given problem. In line with this argumentation, Schwaighofer et al (2016) found that the benefits of worked examples compared to problem solving were lower the higher fluid intelligence was. In that study, the moderating role of fluid intelligence was independent of working memory capacity and shifting.…”
Section: Aptitude Treatment Interactions In the Context Of Complex Lesupporting
confidence: 68%
“…In addition to task complexity, other context characteristics such as time constraints may play a role for ATIs. In the study by Schwaighofer et al (2016) the effectiveness of worked examples was not moderated by working memory capacity. One plausible reason could be that learners did not have to work under time pressure.…”
Section: Aptitude Treatment Interactions In the Context Of Complex Lementioning
confidence: 99%
See 3 more Smart Citations